2004
DOI: 10.1029/2003gl019282
|View full text |Cite
|
Sign up to set email alerts
|

Linking pressure and saturation through interfacial areas in porous media

Abstract: [1] Using transparent microfluidic cells to study the twophase properties of a synthetic porous medium, we establish that the interfacial area per volume between nonwetting and wetting fluids lifts the ambiguity associated with the hysteretic relationship between capillary pressure and saturation in porous media. The interface between the nonwetting and wetting phases is composed of two subsets: one with a unique curvature determined by the capillary pressure, and the other with a distribution of curvatures do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
107
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 15 publications
(15 reference statements)
7
107
2
Order By: Relevance
“…These curves are all found to be hysteretic. In the recent experiments by Cheng et al (2004), a nw -P c -S w surfaces are obtained. They find that the drainage and imbibition surfaces have a difference of only 2.77%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These curves are all found to be hysteretic. In the recent experiments by Cheng et al (2004), a nw -P c -S w surfaces are obtained. They find that the drainage and imbibition surfaces have a difference of only 2.77%.…”
Section: Introductionmentioning
confidence: 99%
“…3. There are some experimental studies where a nw -S w curves are produced (see, e.g., Cheng et al 2004;Chen and Kibbey 2006). These curves are all found to be hysteretic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[60] As it was mentioned above, theoretical, numerical, and experimental results have shown that it is crucially important to include interfacial area for a complete description of two-phase flow in porous media [see e.g., Gray, 1990, 1993b;Held and Celia, 2001;Cheng et al, 2004;Joekar-Niasar et al, 2010b;Hassanizadeh, 2011, 2012].…”
Section: Resultsmentioning
confidence: 99%
“…[5] Recently, two-phase flow studies were performed using photo-resist micromodels that had flow patterns based on stratified percolation [Cheng, 2002;Pyrak-Nolte et al, 2008;Cheng et al, 2004Cheng et al, , 2007Liu et al, 2011]. In these studies, distributions of the two phases in the flow network during quasi-static drainage and imbibition were visualized.…”
Section: Introductionmentioning
confidence: 99%